2021
DOI: 10.1002/eem2.12220
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Ionic Thermoelectric Supercapacitor for Integrated Energy Conversion‐Storage

Abstract: Converting low‐grade waste heat into usable electricity and storing it simultaneously requires a new technology that realize the directional migration of electrons or ions under temperature difference and enrichment on the electrodes. Although the urgent demand of energy conversion‐storage (ECS) has emerged in the field of wearable electronic, achieving the integrated bi‐functional device remains challenge due to the different mechanisms of electrical transportation and storage. Here, we report an ionic thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Over the past few years, giant thermopowers of the order of 10 mV K −1 have been reported frequently in ion conductors (5)(6)(7)(8)(9)(10)(11)(12)(13) or mixed ion-electron conductors (14)(15)(16). The greatly enhanced thermopowers compared with the best electronic thermoelectric materials and reasonable ionic conductivity allow more sensitive thermal sensing, especially for small temperature difference occasions such as the human body thermal monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, giant thermopowers of the order of 10 mV K −1 have been reported frequently in ion conductors (5)(6)(7)(8)(9)(10)(11)(12)(13) or mixed ion-electron conductors (14)(15)(16). The greatly enhanced thermopowers compared with the best electronic thermoelectric materials and reasonable ionic conductivity allow more sensitive thermal sensing, especially for small temperature difference occasions such as the human body thermal monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obtained Seebeck coefficient is basically on the order of mV K –1 , which shows a broad prospect in low-grade heat harvesting . Currently, much research on i-TE systems has been reported based on ionic liquids, polyelectrolytes, and inorganic salt–polymers. Unfortunately, the ionic conductivity of these systems is several orders of magnitude lower than that of normal electronic conductors.…”
mentioning
confidence: 99%
“…The ionic thermoelectric capacitor (ITEC) based on LFICE-4 was fabricated for the conversion and store of heat into electricity, , and the schematic diagram of ITEC is shown in Figure a. The voltage variation of ITEC connected with a 1 kΩ external load to Δ T and the operating principle of ITEC are shown in Figure b,c.…”
Section: Resultsmentioning
confidence: 99%
“…59 Moreover, after 6 months, S i presents no significant change (Figure S13), further indicating that the assembled thermoelectric generator based on LFICE-4 has a long-term stable thermoelectric performance. The ionic thermoelectric capacitor (ITEC) based on LFICE-4 was fabricated for the conversion and store of heat into electricity, 32,58 and the schematic diagram of ITEC is shown in Figure 9a. The voltage variation of ITEC connected with a 1 kΩ external load to ΔT and the operating principle of ITEC are shown in Figure 9b,c.…”
Section: ■ Introductionmentioning
confidence: 99%